1999
DOI: 10.1590/s0004-282x1999000600007
|View full text |Cite
|
Sign up to set email alerts
|

Sintomas psiquiátricos entre pacientes com demência atendidos em um serviço ambulatorial

Abstract: RESUMO -Pacientes portadores de quadros demenciais frequentemente apresentam uma série de sintomas neuropsiquiátricos que incluem distúrbios do humor, delírios, alucinações, sintomas vegetativos e alterações da atividade psicomotora. Este estudo foi desenhado com o objetivo de investigar a prevalência de morbidade psiquiátrica entre os pacientes com o diagnóstico clínico de demência (ICD-10) atendidos na clínica de memória da Santa Casa de São Paulo entre fevereiro de 1997 e maio de 1998. O estado mental e cog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
2
0
7

Year Published

2000
2000
2016
2016

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 29 publications
3
2
0
7
Order By: Relevance
“…In similar studies mentioned before, about the profile of patients assisted at university ambulatory service, 69.3% of patients with dementia reported the presence of sadness and/or loss of interest for things in SRQ-20 (Self Reporting Questionnaire) 15 . Probably, this higher prevalence occurred because depressive symptomatology was described, and not the diagnosis of depressive disorder as in the present study.…”
Section: Discussionsupporting
confidence: 55%
See 1 more Smart Citation
“…In similar studies mentioned before, about the profile of patients assisted at university ambulatory service, 69.3% of patients with dementia reported the presence of sadness and/or loss of interest for things in SRQ-20 (Self Reporting Questionnaire) 15 . Probably, this higher prevalence occurred because depressive symptomatology was described, and not the diagnosis of depressive disorder as in the present study.…”
Section: Discussionsupporting
confidence: 55%
“…With regards to other demographic factors, 51.3% of the patients assisted were married, 34% widowed, and the majority of the samples (54%) had from 1 to 4 years of education. Almeida 15 , studying the prevalence of psychiatric symptoms in patients from a university ambulatory service, described a similar sample, in which 60% were women, 49.3% married, but with fewer years of education, as 37.3% reported they had never been to school. Vale et al 16 has also found similar results in which 57.3% were married and 27.6% widowed with fewer years of education (on average 3 years of education) in patients from an ambulatory of a tertiary hospital.…”
Section: Discussionmentioning
confidence: 98%
“…Alterações do comportamento podem ser observadas em praticamente metade desses indivíduos em estudos transversais 7 , embora a detecção de vários desses sintomas dependa, com frequência, de informações fornecidas pelo cuidador do paciente. O estudo de Burns et al 8 é um exemplo das dificuldades e discrepâncias que podem ocorrer durante a avaliação desses sintomas.…”
unclassified
“…A alta prevalência de sintomas depressivos na DA e em demências, de maneira geral, já foi demonstrada por estudos prévios 12,13,20 . Alterações do sono e vigília estavam entre os sintomas mais encontrados nos pacientes com DA com 54,3%.…”
Section: Artigo Originalunclassified
“…Os sintomas comportamentais estão entre as principais causas de sobrecarga do cuidador do paciente com demência, relacionando-se a maiores níveis de estresse nestes cuidadores 9,10 , visto que sua importante prevalência e impacto já são reconhecidos na prática clínica 11 . Muitos estudos têm demonstrado que sintomas neuropsiquiátricos são comuns tanto em pacientes com DA quanto naqueles com DV 8,12,13 . Um destes estudos 13 Apatia, delírios e alucinações foram significativamente mais freqüentes na DM.…”
Section: Introductionunclassified